Visualizing the Allocation and Death of Objects. - Guyer, Samuel Z.; Veroy, Raoul L.; Ricci, Nathan P. (Tufts University. Tisch Library., 2017)
We present memory allocation and death plots, a visualization technique for showing both which method an object is allocated in a Java program, and in which method that object eventually dies. This relates the place in a program's execution where memory is first used to the place it is no longer used, thus helping the programmer to better understand the memory behavior of a program.; Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.